Mobile Internet Access and the Desire to Emigrate - Joop Age Harm Adema; Cevat Giray Aksoy; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper, we present theory and global evidence on how mobile internet access affects desire and plans to emigrate. Our theory predicts that mobile internet access increases desire and plans to emigrate. Our empirical analysis combines survey data on 617,402 individuals from 2,120 subnational districts in 112 countries with data on worldwide 3G mobile internet rollout from 2008 to 2018. We show that an increase in mobile internet access increases the desire and plans to emigrate. Instrumenting 3G rollout with pre-existing 2G infrastructure suggests that the effects are causal. The effect on the desire to emigrate is particularly strong in high-income countries and for above-median-income individuals in lower-middle-income countries. In line with our theory, an important mechanism appears to be that access to the mobile internet lowers the cost of acquiring information on potential destinations. In addition to this, increased internet access reduces perceived material well-being and trust in government. Using municipal-level data from Spain, we also document that 3G rollout increased actual emigration flows.
Keywords: F20; L86; D83; 330; migration aspirations; migration intentions; internet access